Interfaith Harmony and Cultural Dynamics in Mbawa Village, Indonesia - Nursani, Nursani; Syahbuddin, Syahbuddin; Suparjan, Edy (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
In Indonesia, religious life is a crucial aspect of national identity, as reflected in the 1945 Constitution. In Mbawa, a village in Donggo Ipa, religious diversity and local cultural values, such as tolerance and mutual respect, play a key role in fostering social harmony and preventing interfaith conflict. This study aims to analyze interfaith harmony and cultural dynamics in Mbawa Village, Indonesia, focusing on the practices of social and cultural tolerance. Employing a descriptive qualitative research method, data were collected through observation, interviews, and documentation techniques. The findings reveal that interfaith tolerance in Mbawa Village is fostered through a strong kinship system, the Kaco'i Angi culture, and the practice of mutual assistance, supporting robust social harmony. The study concludes that interfaith tolerance in Mbawa Village reflects a deep integration of cultural and religious elements. The implications of this study suggest the need for policies supporting the preservation of cultural rituals like Raju to strengthen communal solidarity.